Good and Justice in the Context of Environmental Ethics - Nikolai Mihailov; Lidia Sakelarieva (Studia Ecologiae et Bioethicae)
The article is an attempt to review some basic ethical concepts in their historical and substantive development, within the context of the environment and environmental knowledge. It also tries to answer the question whether there is a difference between traditional and environmental ethics. The comparative-historical method is used, which considers some classical ethical concepts and their interpretations related to the environment. The concepts of classical and modern scientists are also analyzed. The authors consider whether these concepts should be supplemented with new content in this area or should be reformulated in terms of moral relevance not only for the human community, but also for all non-human inhabitants of the environment.  The article explores issues about the origin of morality, as well as some ideas about the moral status of attitudes among primates. More important conclusions are that ethics and environmental knowledge must be developed in cooperation in order to explain and form moral consciousness, a new type of ethos that does not allow indifference to the environment in human interaction with it, and that moral considerations should contain not only prescriptions for due human behavior in human society, but also obligations to non-human inhabitants of nature or to the environment.